Potensi sentra olahan ubi kayu dan mitigasi bencana di Desa Kranggan, Galur, Kulon Progo - Paramita, Brigitta Laksmi; Pratama, Sergio; Novianti, Fatimah; Gurusinga, Christophel; Satriani, Amanda Putri Eriandina; Marhaeni, Maria Btari Larasati; Lo, Christina Natalia Kharis; Katelya, Dea; Yuniarka, Gisela Radiastasha; Putrianti, Pita Desi; Malau, Deon Natanael (Jurnal Atma Inovasia, 2022)
Kuliah Kerja Nyata (KKN) are part of a mandatory activity to fulfill student obligations, namely community service, KKN in batch 80 is carried out online due to the covid-19 pandemic. Therefore, this research was conducted to fulfill the task given by Atma Jaya University Yogyakarta. The Kranggan Village area is one of the villages located in the Galur sub-district, Kulon Progo Regency which is located close to the southern coast of the island of Java. Therefore, it is necessary to have comprehensive efforts in policy making to reduce the risk caused by natural disasters such as doing mitigation. In addition, this study aims to educate the Kranggan village community in increasing search results from cassava plants, where the Kranggan village area has 91.0 hectares of land for cassava plants in 2018. Data collection techniques in this research are observation, collection of literature studies from the internet and discussions with lecturers. The results of this study were made together with a pocket book or e-book entitled "Potency of Kranggan Village, Processed Cassava" and an e-book or pocket book "Disaster Mitigation". The target of this KKN program is the formation of a home industry that is able to compete in the market and is managed directly by the Kranggan village community and provides education if a natural disaster occurs, so that the community understands what actions to take in certain situations. Therefore, Group 79 chose to make an e-book on village potential on the use of cassava and disaster mitigation counseling. The results of this study are expected to be useful in the future for the people of Kranggan Village in increasing their income from making cassava chips in addition to the work of the majority of the population is farming and is expected to be useful for the people of Kranggan Village to always be responsive and alert in taking action to deal with natural disasters.